SUN-LB127 In Experimental Peripheral Arterial Disease MIR29a Modulation Improves Perfusion Recovery and Muscle Function to a Greater Extent Than ADAM12 Augmentation in Mice With Type 2 Diabetes - Lamin, Victor (J Endocr Soc, 2020)
Diabetes Mellitus (DM) is a major risk factor for developing peripheral arterial disease (PAD) and individuals with DM have worse PAD outcomes but the molecular mechanisms involved are poorly understood. We previously identified a disintegrin and metalloproteinase gene 12 (ADAM12) as a key genetic modifier of post-ischemic perfusion recovery in experimental PAD that it is regulated by miR29a through direct interaction. In ischemic hind limbs non-diabetic mice, miR29a expression is downregulated and allows ADAM12 upregulation. However, in ischemic hind limbs of type 2 DM (DM2) mice miR29a expression remains elevated and prevents ADAM12 upregulation. Hence, we hypothesized that inhibition of miR29a or augmenting ADAM12 would improve the impaired perfusion recovery typical of mice with DM2 in experimental PAD. Here, in mice with DM2 we compare the therapeutic effectiveness of miR29a inhibition (miR29aINH) to ADAM12 gene overexpression on perfusion recovery in experimental PAD. 26 - 28 weeks old C57BL/6 mice on high fat diet were randomized into 3 treatment groups: sham (saline), miR29aINH, or ADAM12 plasmid. Agents were delivered by micro-bubbles at 5 days and 1 day pre-surgery. Experimental PAD was achieved by unilateral ligation and excision of the femoral artery of the left hind limb. The right hind limb serves as non ischemic control. Peripheral blood flow is measured by Laser Speckle Contrast Imaging. Tibialis anterior contractile function was assessed using an Aurora 300B-LR. ADAM12 and miR29a expression levels were quantified using qPCR on day 3 post surgery since perfusion at this point is similar between the experimental groups. Data are expressed as means ± SEM. Statistical significance of P < 0.05 as significant is performed with the independent Student’s t-test. Gene expression analysis 3 days post ischemia showed miR29a inhibitor reduced miR29a levels (miR29aINH: 0.70±0.06, n=5, ADAM12: 0.62±0.06, n=4, p=0.3938 and Sham: 1.02±0.06, n=5, p= 0.004 for miR29aINH vs Sham) and increased ADAM12 expression to a greater extent than ADAM12 gene transfer (miR29aINH: 208.62±24.52, n=3, ADAM12: 20.71±2.98, n=4, p= 0.0003 and Sham: 11.75±4.94, n=4). 3 weeks post-surgery, there was significantly higher perfusion recovery in mice treated with miR29aINH compared to ADAM12 gene transfer (miR29aINH: 97.59±6.14, n= 10, ADAM12: 58.45±4.87, n=8, p=0.002 and Sham: 42.52±5.35, n=5). Muscle contraction in the ischemic limb was >2-fold stronger in the miR29aINH treated mice compared to ADAM12 gene transfer (miR29aINH: 0.54±0.08, n=7, ADAM12: 0.26±0.06, n=7, p= 0.0170 and Sham: 0.17±0.06, n=6). Our result reveals for the first time that inhibiting elevated microRNAs may be a more effective therapeutic approach than gene transfer to improve blood flow and muscle function in type 2 DM and PAD.